Contact analysis using Trefftz and interface finite elements - Wang, Ke Y.; Dhanasekar, Manicka; Qin, Qing H.; Kang, Yi L. (Computer Assisted Methods in Engineering and Science, 2006)
Hybrid- Trefftz (HT) finite element (FE) analysis of two-dimensional elastic contact problems is addressed with the aid of interface elements and an interfacial constitutive relation. This paper presents the formulation of a four-noded HT finite element for discretizing the contacting bodies and a four-noded interface element that could be embedded in the prospective contact zone for simulating the interaction behaviour. Due to the superior performance, the Simpson-type Newton- Cotes integration scheme is utilized to compute interface element formulation numerically. In order to evaluate the applicability of the present approach two benchmark examples are investigated in detail. Comparisons have been made between the results by the present approach and analytical as well as traditional FE solutions using ABAQUS software.